When do nice guys finish last? Prosociality and the psychological model of CEO ‐firm matching - Keum, Dongil Daniel; Bhatia, Nandil (Strategic Management Journal, 2025)
Abstract Research Summary Prosocial CEOs, characterized by greater concern for their employees, enhance employee motivation but incur higher costs when implementing layoffs. We develop a psychological model of CEO‐firm matching wherein negative industry shocks requiring downsizing asymmetrically erode the match quality for prosocial CEOs. Leveraging increases in Chinese import competition, we show that layoff pressures lead to higher rates of both forced and voluntary turnover among prosocial CEOs. They are succeeded by less prosocial CEOs who are externally recruited, use less employee‐friendly language, lean Republican in political orientation, or are less likely to volunteer at charities. Our study highlights psychological characteristics as a key consideration in the executive labor market and draws attention to the “first‐stage” selection dynamics that shape the types of CEOs who lead firms. Managerial Summary Which firms CEOs choose to join and which CEOs are selected or retained by boards depend not only on their skills but also on the fit between their ‘personality’ and the firm's needs. We show that during industry downturns that require aggressive downsizing, prosocial CEOs are more likely to depart voluntarily, and boards actively replace them with low‐prosocial “wartime” CEOs. This dynamic nature of the CEO‐firm fit provides insights into why and when previously effective leadership may become ineffective and empirical grounds for the common distinction between peacetime and wartime CEOs. A key implication is that increasing Chinese import competition has shaped not only firm economic activities but also the psychological profiles of business leaders.